2019
DOI: 10.1038/s41598-019-54320-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and degradation kinetics of TiO2/GO composites with highly efficient activity for adsorption and photocatalytic degradation of MB

Abstract: Poriferous TiO2/GO (denoted as TGO-x%) photocatalysts with ultrathin grapheme oxide (GO) layer were prepared by a hydrothermal method, the adsorption and photocatalytic degradation and its kinetics about Methylene blue(MB) were studied systematically. All the TGO-x% showed improved adsorption and photodegradation performance. TGO-25% had excellent adsorptivity while TGO-20% exhibit the highest visible light photocatalytic degradation activity. The adsorption capacity for TGO-25% was 20.25 mg/gcatalyst along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Using XRD patterns, Min et al [50] also showed that all the peaks for the TiO 2 /GO composites were Using XRD patterns, Min et al [50] also showed that all the peaks for the TiO 2 /GO composites were indexed to the anatase phase of TiO2, without peaks of layered GO and these results demonstrate that the GO was considerably reduced to graphene sheet during the solvothermal reaction. characteristic of graphene begins to appear, which can be explained by possible partial reduction of GO.…”
Section: Preparation Of Graphene Oxidementioning
confidence: 99%
“…Using XRD patterns, Min et al [50] also showed that all the peaks for the TiO 2 /GO composites were Using XRD patterns, Min et al [50] also showed that all the peaks for the TiO 2 /GO composites were indexed to the anatase phase of TiO2, without peaks of layered GO and these results demonstrate that the GO was considerably reduced to graphene sheet during the solvothermal reaction. characteristic of graphene begins to appear, which can be explained by possible partial reduction of GO.…”
Section: Preparation Of Graphene Oxidementioning
confidence: 99%
“…Recently, the nanohybrids consisting of two geometrically dissimilar nanofillers will give a full play to the advantages of each nanofillers and exhibit promising synergistic effect, which can exert a more positive influence on the properties of polymers 50,51 . Typically, the nanomaterials with large surface area, such as halloysite nanotubes, carbon nanotubes, grapheme nanosheets and mesoporous silica, were often used as the nanocarriers to immobilize other functional Nps 52‐54 . In the field of UV‐shielding polymer composites, some significant researches also developed the UV‐shielding nanohybrids consisting of anti‐UV Nps and nanocarriers.…”
Section: Recent Advances In Highly Efficient Uv‐shielding Compositesmentioning
confidence: 99%
“…Figures 9a and 9b show the deconvolution of the C (1s) peak for the reference sample (bare TiO 2 powder; Figure 9a) and for the as-deposited TiO 2 @C nanocomposite deposited at 8 kV (Figure 9b). The C (1s) peak of the TiO 2 NPs powder is fitted with only one component at 285 eV, corresponding to adventitious carbon contaminants [34] (C-C and/or C-H), whereas four components at 285, 286.7, 288.3, and 289.1 eV were utilized to fit the C (1s) peak obtained from the TiO 2 @C deposited at 8 kV. The first peak at 285 eV is due to the graphitic carbon bonds (alkyl) C-C and/or C-H formed at the surface of the nanocomposites, whereas the three others correspond to C-O, C═O and/or O-C-O and/ or O-C═O/COOH bonds of the carbonate-like species due to the oxidation of carbon species, [28,35] as they are also found in C-TiO 2 prepared by wet chemical reactions using different carbon precursors by Kim et al [36] The highest C (1s) energy peaks at 288.3 and 289.1 eV are also identified in TiO 2 @C prepared by wet chemical methods and different molecular carbon precursors.…”
Section: Morphology and Structure Of Deposited Filmsmentioning
confidence: 99%